Assessing the needs of grandparents of preterm infants in neonatal intensive care units: a cross-sectional study - Huang, Huamin; Tao, Jingyun; Lei, Ying; Chen, Rui; Fang, Haixia (Frontiers in Psychology, 2024)
Background: Globally, there is an increasing trend in the incidence of premature births and low birth weight. Neonatal intensive care unit (NICU) care has become indispensable for these newborns. Nevertheless, this mode of care poses substantial economic, psychological, and health challenges to the families of preterm infants. Despite abundant evidence concerning the parents' needs in NICU, the grandparents' needs-vital family members-are frequently disregarded. This exploratory study aims to assess the grandparents' needs of preterm infants in the NICU, exploring the impact of demographic elements on these needs to offer guidance for clinical care practices. Methods: This study employed a cross-sectional design and the Chinese version of the NICU Family Needs Inventory (NICU-FNI) to investigate grandparents' needs. A total of 280 grandparents participated in the study, providing data by completing structured questionnaires related to their demographic profiles and needs. Statistical analyses were utilized to analyze the data, including descriptive statistics, chi-square tests, Pearson correlation, and multiple linear regression.Results: Six items about Assurance emerged as significant among the top ten important needs, with two items for Information, one item for Proximity, and one item for Support; among the least important needs, nine items related to Comfort and Support were identified. The subscale Assurance achieved the highest mean score of 4.07 ± 0.49, followed the subscales by "Information" and Proximity, both registering mean scores of 3.50 ± 0.47 and 3.50 ± 0.46, respectively. This explorative study identified a correlation between the needs for Assurance and the employment status, place of residence, gestational age, and birthweight (p<0.05). Employment status, place of residence, and gestational age were identified as significant correlates for Assurance (p<0.05).The foremost need identified by grandparents is the Assurance of quality care for preterm infants, closely followed by the demand for thorough Information and the ability to be in Proximity to the infant. This exploratory study highlights that mitigating the strain on families with preterm infants, as well as recognizing and meeting the needs of grandparents, is of paramount importance.